Beyond abortion: impacts of the expanded global gag rule in Kenya, Madagascar and Nepal. Issue 7 (19th July 2022) - Maistrellis, Emily; Juma, Kenneth; Khanal, Aagya; Kimemia, Grace; McGovern, Terry; Midy, Anne-Caroline; Rakotondratsara, Mamy Andrianina; Ratsimbazafy, Marie Rolland; Ravaoarisoa, Lantonirina; Razafimahatratra, Mamy Jean Jacques; Tamang, Anand; Tamang, Jyotsna; et al.
Abstract : Since 1984, Republican administrations in the US have enacted the global gag rule (GGR), which prohibits non-US-based non-governmental organisations (NGOs) from providing, referring for, or counselling on abortion as a method of family planning, or advocating for the liberalisation of abortion laws, as a condition for receiving certain categories of US Global Health Assistance. Versions of the GGR implemented before 2017 applied to US Family Planning Assistance only, but the Trump administration expanded the policy's reach by applying it to nearly all types of Global Health Assistance. Documentation of the policy's harms in the peer-reviewed and grey literature has grown considerably in recent years, however few cross-country analyses exist. This paper presents a qualitative analysis of the GGR's impacts across three countries with distinct abortion laws: Kenya, Madagascar and Nepal. We conducted 479 in-depth qualitative interviews between August 2018 and March 2020. Participants included representatives of Ministries of Health and NGOs that did and did not certify the GGR, providers of sexual and reproductive health (SRH) services at public and private facilities, community health workers, and contraceptive clients. We observed greater breakdown of NGO coordination and chilling effects in countries where abortion is legal and there is a sizeable community of non-US-based NGOs working on SRH. However, we found that the GGR fractured SRH service delivery in all countries, irrespective of the legal status of abortion. Contraceptive service availability, accessibility and training for providers were particularly damaged. Further, this analysis makes clear that the GGR has substantial and deleterious effects on public sector infrastructure for SRH in addition to NGOs.